(untitled) (Bangladesh Journal of Neurosurgery, 2020)
Objective: The objective of the study was to compare the surgical outcome between Bilateral Laminotomy, Laminectomy and Unilateral approach in Lumber Spinal Stenosis. Methods: One hundred forty four (144) patients were going to underwent three prospective surgery such as Bilateral Laminotomy (48 patients), Laminectomy (48 patient) and Unilateral approach (48 patients). This study conducted between 2009 to 2014 at private medical hospitals in Dhaka. All the patients ages are e” 40. All the patients were observed prospectively. Clinical outcomes for back and leg pain were analyses using Oswestry Disability Index (ODI) questionnaires and Swiss score. Results: Satisfactory decompression was accomplished in all patients. The complications were less in patients who had experienced Unilateral Laminotomy rather than Bilateral Laminotomy and Laminectomy. Mean age of patients were 52.16+/ - 6.87 years with the range of 40-68 years. Among them 101 patients are male (70.11%) and 43 patients are female (29.99%). The rates of improvements are 79.17% in Laminectomy, 85.1% in Bilateral Laminotomy and 91.9% in Unilateral Laminotomy. From here unilateral Laminotomy have quite better results than others. Minimum follow up period was 2 years. Conclusion: Unilateral Laminotomy has a satisfactory outcome in Lumber Spinal Stenosis surgery in comparison to rest of two approaches. Postoperative complications were minimum in respect to blood loss, hospital stay and revision surgery. Bang. J Neurosurgery 2020; 9(2): 105-110